Cellulose Amorphization by Swelling in Ionic Liquid/Water Mixtures: A Combined Macroscopic and Second-Harmonic Microscopy Study - Glas, Daan; Paesen, Rik; Depuydt, Daphne; Binnemans, Koen; Ameloot, Marcel; De Vos, Dirk E.; Ameloot, Rob (ChemSusChem, 2015)
Amorphization of cellulose by swelling in ionic liquid (IL)/water mixtures at room temperature is a suitable alternative to the dissolution–precipitation pretreatment known to facilitate enzymatic digestion. When soaking microcrystalline cellulose in the IL 1‐ethyl‐3‐methylimidazolium acetate containing 20 wt % water, the crystallinity of the cellulose sample is strongly reduced. As less than 4 % of the cellulose dissolves in this mixture, this swelling method makes a precipitation step and subsequent energy‐intensive IL purification redundant. Second‐harmonic generation (SHG) microscopy is used as a structure‐sensitive technique for in situ monitoring of the changes in cellulose crystallinity. Combined optical and SHG observations confirm that in the pure IL complete dissolution takes place, while swelling without dissolution in the optimal IL/water mixture yields a solid cellulose with a significantly reduced crystallinity in a single step. Soaking as the solution: Soaking of cellulose ionic liquid/water mixtures results in a reduced crystallinity (amorphization). The evolution of cellulose crystallinity is studied in situ by second‐harmonic generation (SHG) microscopy. These results show the potential of soaking in ionic liquid/water mixtures as an alternative cellulose pretreatment method, with the main advantage of avoiding energy‐intensive IL purification, as required in dissolution–precipitation.